P169 Is there an association between receiving a respiratory specialist review and receipt of discharge bundle when admitted for asthma?. (12th November 2019) - Adamson, A; Robinson, S; Roberts, CM; Quint, JK; Calvert, J
Abstract : Introduction: Respiratory specialist review is recommended in people admitted to secondary care with acute asthma 1 as there is evidence that patient self-management education reduces readmissions. 2 Patient education forms the bulk of the discharge bundle recommended for asthma patients before discharge. Our analysis is the first to assess whether specialist review is associated with receipt of a discharge bundle and its individual elements in acute asthma patients in secondary care. Methods: The Royal College of Physicians National Asthma and COPD Audit Programme (NACAP) began a continuous audit on acute asthma treatment in secondary care in November 2018. 170 hospitals in Britain provided data on acute asthma admissions from November 2018 to March 2019. Data were collected on patient characteristics and care received. We used multi-level logistic regression including hospital as a random intercept to assess the effect of specialist review on receipt of a discharge bundle and individual discharge elements. Results: 10, 428 asthma admissions were inputted during the audit, of which 10, 242 (98.2%) were suitable for analysis. 76.8% of patients (N=7870) received a respiratory specialist review during their hospital stay, and 48.1% (N=4926) of patients received a discharge bundle. After excluding patients who self-discharged or died in hospital (N=221), patients who received a respiratory specialist review were 33 times more likely to receive a discharge bundle compared to those who did not receive a respiratory specialist review, after adjusting for hospital (adj-odds ratio=32.9, 95% CI=26.0 to 41.5). Receipt of a specialist review was significantly associated with receipt of each of the elements of good practice care recommended by NICE/BTS before discharge (see table 1). Conclusion: Receiving a respiratory specialist review significantly increases the likelihood of acute asthma patients receiving a discharge bundle and elements of good practice care. References: National Institute for Health and Care Excellence. ( 2013). Asthma (NICE Quality Statement 9). Available at: https://www.nice.org.uk/guidance/qs25/documents/previous-version-of-quality-standard-2 [Date accessed 05 July 2019] SIGN 153. (2016). BTS/ SIGN British Guideline for the management of asthma . Available at https://www.sign.ac.uk/assets/sign153.pdf [Date accessed 05 July 2019]